O arcaísmo da modernidade : mobilidade urbana, bicicletas e o trânsito em Maringá - Oliveira, Eduardo Simões Flório de (2016)
The perspective of this dissertation is to diagnose the geographical and cultural aspects involving urban mobility with bicycles in the city of Maringá, Paraná, signaling to awareness policies and changes in the infrastructure in order to enable the use of this means of transportation and thus improve the conditions in urban displacements. This is a critic about the automotive dominance, which has failed in several aspects since the cities based on this urban model are too costly and environmentally polluted. It will also be investigated the historical moment in which the preference for individual motorized transport in detriment of others was consolidated, since Maringa already has had another picture in these aspects. The methodology adopted in the survey has a multidimensional character involving the sources crossing from: collection of statistical data, documentary research, bibliographic research, comparative analysis and semi-directed interviews, in order to extract qualitative information of the deponents. It will also address the right to urban areas, because we believe that the predominance of the motorized means in roads precludes citizens their "right to the city", therefore a new meaning to the city is necessary.